Haplotype-resolved genomes provide insights into structural variation and gene content in Angus and Brahman cattle - Wai Yee Low (Nature Portfolio, 2020)
Taurine and indicine cattle have different desirable traits making them better adapted to different climates across the world. Here, Low et al. describe a pipeline to produce haplotype-resolved, chromosome-level genomes of Angus and Brahman cattle breeds from a crossbred individual and report on comparisons of the two genomes.